Debate: One of the Key Factors to Improving Students’ English Language Speaking Skills - Bunheng Ban; Sina Pang; Sereyrath Em (Journal of General Education and Humanities, 2023)
Over the last decade, English debates have become very popular in Cambodia. Most students with experience debating in English tend to have good English-speaking skills. It is interesting to learn more about the effect of debating in English on these students’ English language skills. Thus, this research paper aims to look into the debate's impact on the English language speaking skills of English as a Foreign Language (EFL) university students who have participated in debate competitions in Cambodia. It was a case study at The University of Cambodia (UC). The qualitative approach was used, and the total participants in the study were ten undergraduate students who participated in a debate competition in the English language in Phnom Penh, Cambodia. The study results showed that the respondents positively perceived a debate. They reported that debate improved their English language speaking skills. In conclusion, the debate has positively impacted my speaking performance and other critical thinking skills. Therefore, it should be added to the university's program as an extracurricular activity.